2017
DOI: 10.1371/journal.pone.0176111
|View full text |Cite
|
Sign up to set email alerts
|

Complementing the topsoil information of the Land Use/Land Cover Area Frame Survey (LUCAS) with modelled N2O emissions

Abstract: Two objectives of the Common Agricultural Policy post-2013 (CAP, 2014–2020) in the European Union (EU) are the sustainable management of natural resources and climate smart agriculture. To understand the CAP impact on these priorities, the Land Use/Cover statistical Area frame Survey (LUCAS) employs direct field observations and soil sub-sampling across the EU. While a huge amount of information can be retrieved from LUCAS points for monitoring the environmental status of agroecosystems and assessing soil carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
1
14
2
1
Order By: Relevance
“…To our knowledge, this is the first time that a bulk density map for soils was generated and used to estimate the N 2 O-N emissions from managed European peatlands. Our work is in line with studies showing that the drained peatlands in Europe are in a stage of severe degradation and suggests that they emit considerable amounts of N 2 O-N. Less than 6 × 10 6 ha of agriculturally used peatlands (cropland and grassland) emit over 100 Gg N 2 O-N year −1 , equivalent to 25 % of soil N 2 O emissions from the entire agriculture land of EU-28 47 . In this study, the estimated N 2 O-N emissions from European managed peatlands are twice the value of those calculated using IPCC default emission factors.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the first time that a bulk density map for soils was generated and used to estimate the N 2 O-N emissions from managed European peatlands. Our work is in line with studies showing that the drained peatlands in Europe are in a stage of severe degradation and suggests that they emit considerable amounts of N 2 O-N. Less than 6 × 10 6 ha of agriculturally used peatlands (cropland and grassland) emit over 100 Gg N 2 O-N year −1 , equivalent to 25 % of soil N 2 O emissions from the entire agriculture land of EU-28 47 . In this study, the estimated N 2 O-N emissions from European managed peatlands are twice the value of those calculated using IPCC default emission factors.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison with Lugato et al (2017), we found similar results for the Mediterranean latitudes (about 1 kg N-N 2 O ha -1 y -1 ), while we predicted significantly lower emissions for Central Europe (1.1 kg N-N 2 O ha -1 y -1 , this study), as well as at higher latitude (0.96 kg N ha -1 y -1 , this study), compared to 3 kg N-N 2 O ha -1 y -1 forecasted by Lugato et al (2017). Indeed, lower emissions at high latitudes were also reported by other studies (World Bank;Eurostat, 2017;Stehfest and Bouwman, 2006;Wells et al, 2018).…”
Section: Effect Of Climate On N2o and Ch4 Emissionsmentioning
confidence: 96%
“…The estimation and the projection of N 2 O emissions in the historical and the climate change scenarios were in line with other model integrations over Europe. Lugato et al (2017) estimated averaged emissions ranging from 1.18 to 2.63 kg N-N 2 O ha -1 y -1 in the period 2010-2014 for both cropland and grasslands production systems with the DayCent model.…”
Section: Effect Of Climate On N2o and Ch4 Emissionsmentioning
confidence: 99%
“…The Joint Research Council (JRC) applies this model at the EU scale on the LUCAS sample points (Ballabio, Panagos, & Monatanarella, 2016;Orgiazzi, Ballabio, Panagos, Jones, & Fernández-Ugalde, 2018) to estimate carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) emissions in agricultural soils under different scenarios (Lugato, Leip, & Jones, 2018;Lugato, Paniagua, Jones, de Vries, & Leip, 2017;Quemada, Lassaletta, Leip, Jones, & Lugato, 2020) and it is validated for these two parameters. The DayCent model was applied on a 12-year simulation period following the procedure in Lugato et al (2017). More information on the model's setup, validation and associated uncertainties can be found in that publication.…”
Section: Daycent Datasetmentioning
confidence: 99%